GLATIRAMER ACETATE AND PREGNANCY IN WOMEN WITH MULTIPLE SCLEROSIS – RESULTS FROM THE GERMAN MULTIPLE SCLEROSIS AND PREGNANCY REGISTRY. Issue 1 (14th December 2015) - Herbstritt, Sandra; Gold, Ralf; Hellwig, Kerstin
Abstract : Objective: To determine the effect of glatiramer acetate (GLAT) exposure during pregnancy on perinatal outcome in women with multiple sclerosis (MS). Background: MS is one of the most common neurological diseases of the central nervous system, which mainly affects young women of reproductive age. Only limited data are available on whether GLAT exposure during pregnancy has an effect on perinatal outcome. Methods: We compared the outcome of pregnancies of patients with MS exposed to GLAT with pregnancies of unexposed controls. Women with MS were enrolled into the German Multiple Sklerosis and pregnancy registry. Data were assessed with a standardized questionnaire during pregnancy and the postpartum year. Detailed information on course of MS, concomitant medication, pregnancy course and outcome was obtained. Results: We collected data on 230 pregnancies: 135 with exposure to GLAT and 95 MS controls unexposed to disease-modifying therapies (DMTs) during pregnancy. While 25 of the exposed pregnancies are still ongoing we did not document any malformation in the first 110 GLAT exposed pregnancies with at least 6 months postpartum follow up. The rate of spontaneous abortions did not differ compared to unexposed controls. 3 (3.15%) infants of the DMT unexposed women were born with malformations of non-genetic origin and 1 (0.95%) newborn was diagnosed with Wolf Hirschhorn syndrome. Conclusions: GLAT exposure does not constitute a major human teratogen or influence outcome of pregnancy negatively compared to untreated women with MS. Final data including the outcome of ongoing pregnancies will be presented at the time of the meeting.